EFFECTIVENESS OF REFEZO IN INFANTS WITH FUNCTIONAL GASTROINTESTINAL DISORDERS - I.A. Karimzhanov; N.K. Tolipova; A.K. Tursunboev; G.A.Yusupova; G.X.Iskanova; N.A.Israilova; K.Z. Yaxyayeva; M.Q. Togayev. Sh.Sh. Mallayev (The Bioscan, 2024)
The article describes the experience of using Refezo (domperidone) in suspension in young children with regurgitation syndrome. The study group consisted of 60 patients aged 1 month to 1 year who experienced vomiting, regurgitation, flatulence and GER in somatic diseases (pneumonia, bronchiolitis, obstructive bronchitis, sepsis). Group I consisted of 30 children with functional gastrointestinal disorders (FGD), who received basic therapy including the prokinetic drug Refezo. Group II consisted of 30 children with FGD who received only basic therapy. In children with FGD treated with Refezo, the drug was effective in 96% of children, and there were no side effects in the form of individual intolerance, allergic manifestations and neurological disorders.